Pengaruh Model Pembelajaran Kooperatif Type Team Games Tournament Terhadap Hasil Belajar pada Mata Pelajaran IPA di Kelas IV SDIT Ummu Hafidzah Sibiru-Biru - Ekawati, Sri; Harahap, Syarifah Ainun; Ramadhan, Nuri (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to determine the influence of domino card learning media on students' learning outcomes in the material on the structure and function of plants for fourth-grade students at SD Negeri 101928 Rantau Panjang. Additionally, it seeks to compare the learning outcomes between students in an experimental class and a control class at SD Negeri 101961 Timbang Deli. This research employs a quasi-experimental quantitative approach, utilizing pretest and posttest assessments. Two classes, each consisting of 20 students, were involved: one as the experimental group, which used domino card learning media, and the other as the control group, which did not. The results show that the experimental group achieved higher scores, with an average of 92, compared to the control group, which averaged 88. These findings indicate a significant impact of domino card learning media on improving students' science learning outcomes.